Multidrug-Resistant Bacterial Infections in Pediatric Patients Hospitalized at King Abdulaziz University Hospital, Jeddah, Western Saudi Arabia - Fajr A. Saeedi; Moustafa A. Hegazi; Hani Alsaedi; Ahmed Hussain Alganmi; Jawahir A. Mokhtar; Eilaf Majdi Metwalli; Hanaa Hamadallah; Ghassan S. Siam; Abdullah Alaqla; Abdullah Alsharabi; Sultan Ahmed Alotaibi (MDPI AG, 2024)
Multidrug-resistant bacterial infections (MDRIs) constitute a major global threat due to increased patient morbidity/mortality and hospital stay/healthcare costs. A few studies from KSA, including our locality, addressed antimicrobial resistance in pediatric patients. This study was performed to recognize the incidence and clinical/microbiologic features of MDRIs in hospitalized pediatric patients. A retrospective cross-sectional study included pediatric patients < 18 years, admitted to King Abdulaziz University Hospital, between October 2021 and November 2022, with confirmed positive cultures of bacteria isolated from blood/body fluids. Patients' medical files provided the required data. MDR organisms (MDROs) were identified in 12.8% of the total cultures. The incidence of MDRIs was relatively high, as it was detected in 42% of patients and in 54.3% of positive bacterial cultures especially among critically ill patients admitted to the NICU and PICU. Pneumonia/ventilator-associated pneumonia was the main type of infection in 37.8% of patients with MDROs. Klebsiella pneumoniae was the most common significantly isolated MDRO in 39.5% of MDR cultures. Interestingly, a low weight for (no need for their as terminology weight for age is standard and well-known) was the only significant risk factor associated with MDROs (p = 0.02). Mortality was significantly higher (p = 0.001) in patients with MDROs (32.4%) than in patients without MDROs (3.9%). Patients who died including 85.7% of patients with MDROs had significantly longer durations of admission, more cultures, and utilized a larger number of antibiotics than the surviving patients (p = 0.02, p = 0.01, p = 0.04, respectively). This study provided a comprehensive update on the seriously alarming problem of MDROs, and its impacts on pediatric patients. The detected findings are crucial and are a helpful guide to decid for implementing effective strategies to mitigate MDROs.